Overview of Hepatitis B virus (HBV) Infection : Hepatitis B virus (HBV) Infection - Alsulaimany, Faten (Journal of King Abdulaziz University: Science, 2024)
Hepatitis B is a virus that can harm the liver in both the short and long term. The virus can also be transmitted through unsafe injections, unsafe sex, or accidental skin puncture with a sharp object, among other means. The virus is most commonly passed from mother to child during labor and delivery. According to the World Health Organization (WHO), 296 million people will have chronic hepatitis B infection in 2019, with 1.5 million new cases each year. The vast majority of the estimated 820,000 hepatitis B-related deaths in 2019 are due to cirrhosis and hepatocellular carcinoma. (Primary liver cancer). Hepatitis B can be avoided with the help of safe and effective vaccines. The hepatitis B virus causes a liver infection that, if left untreated, can be fatal (HBV). The entire world’s health is jeopardized. It can result in a long-term infection and an increased risk of dying from cirrhosis or liver cancer. You can get a vaccine that protects against hepatitis B and has a high success rate (98% to 100%). A major goal is to prevent long-term health problems and liver cancer, both of which can result from hepatitis B infection. According to the World Health Organization, there are 116 million and 81 million infected people worldwide. According to statistics, chronic hepatitis B infection is most common in the Western Pacific and African regions. The WHO Eastern Mediterranean Region has 60 million cases, South-East Asia has 18 million, Europe has 14 million, and the Americas have 5 million.